1995
DOI: 10.1016/0370-2693(94)01401-w
|View full text |Cite
|
Sign up to set email alerts
|

The analytical value of the corner-ladder graphs contribution to the electron (g − 2) in QED

Abstract: The contributions to the (g-2) of the electron from the corner-ladder graphs in sixth-order (three-loop) QED perturbation theory are evaluated in closed analytical form. The results obtained are in excellent agreement with the most precise numerical evaluations already existing in the literature. Our results allows one to reduce the numerical uncertainty of the theoretical determination of the g-2 of the electron. §

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…, I 18 . The Laurent expansions in ǫ = (4 − D)/2 of the master integrals were calculated in analytical form, by direct calculation (the simpler ones) or by using identities which relate the coefficients of expansions to values of integrals in 4 dimensions already known from previous work [5,6,7,8]. Subsequently, in Ref.[9], we found that the QED contribution of all three-loop graphs can be reduced to a linear combination of the same master integrals, which are therefore the only master integrals needed in the three-loop calculation.…”
mentioning
confidence: 99%
“…, I 18 . The Laurent expansions in ǫ = (4 − D)/2 of the master integrals were calculated in analytical form, by direct calculation (the simpler ones) or by using identities which relate the coefficients of expansions to values of integrals in 4 dimensions already known from previous work [5,6,7,8]. Subsequently, in Ref.[9], we found that the QED contribution of all three-loop graphs can be reduced to a linear combination of the same master integrals, which are therefore the only master integrals needed in the three-loop calculation.…”
mentioning
confidence: 99%
“…As the previous graphs were the last graphs for which the analytical value of the anomaly was still missing, on account the previously known results [4,5,6,7] (5) By using the best numerical value of a e (4 − loop) = −1.557(70) , Ref. [8], and 1/α = 137.0359979(32) , Ref.…”
mentioning
confidence: 99%
“…(11), one finds for instance (16) Similarly, in Ref. [7] the following 7-denominator integral was evaluated…”
mentioning
confidence: 99%
“…21 compares the contributions and uncertainties for g/2. The leading constants for second [64], third [65,66,67] and fourth [68,69,70,71,72] orders,…”
Section: New Determination Of the Fine Structure Constantmentioning
confidence: 99%